Fabrication of natural and magnetic slippery surfaces - Sutherland, Daniel James, author; Kota, Arun K., advisor; Popat, Ketul, committee member; Park, Juyeon, committee member (Colorado State University. Libraries, 2019)
Liquid-infused porous surfaces (LIPS) are a type of low adhesion surfaces. They allow most common solids and liquids to slide off the surface easily. Because of this they are able to reduce the adhesion of food, ice, and even blood platelets to surfaces. As a result, LIPS have applications in reducing food waste, aircraft and powerlines deicing, and hemocompatable implants. However, most LIPS are made of toxic fluorocarbon materials. In this work, in order to eschew toxic fluorocarbon materials, we designed several LIPS made from natural hemp products. The first is an all-natural LIPS made from hemp fibers, which could help reduce or eliminate liquid food waste. The second is an aluminum LIPS that shows excellent anti-icing and de-icing properties. The third is a titanium nanotube LIPS that allows blood to slide off without impinging or clotting. This surface also shows excellent platelet reduction. Finally, we demonstrated a simple way of replicating this LIPS system on multiple metals including copper and steel. Further, we demonstrated a simple fabrication of LIPS on top of the fabricated texture atop a magnetic tape. Magnetic tapes are no longer widely used and they are extremely difficult to dispose of. In this magnetic tape-based LIPS, we were able to use an external magnet to manipulate droplets on the surface of the magnetic tape. This can lead to a microfluidic system with a repurposed substrate and precise manipulation of droplets using a magnetic field.
Keywords: magnetic; oil; surface; natural; icephobic; slippery